Administration of the small public library - Weingand, Darlene E. (American Library Association, 2001)
What is our library's mission statement?. How do we serve our older customers better?. How do I justify the purchase of a new Internet workstation in my library?. How many times should I call the plumber each year?. These questions and more are discussed in the new edition of an old classic. Since the publication of its first edition in 1965, Administration of the Small Public Library has been a gold standard resource for setting up and managing cutting-edge small public library facilities. Completely revised and updated, this fourth edition continues that tradition with many more figures, cas.